Inclusion compounds of multipedal hosts - Nash, Katherine Lindsay Gifford (Department of Chemistry, 2017)
The inclusion properties of three multipedal host compounds have been investigated. The host compounds : hexakis(3-hydroxy-3,3-diphenyl-2-propynyl)benzene (host 1), 1,2,3,5,6, 7-hexakis(3-hydroxy-3,3-diphenyl-2-propynyl)naphthalene (host 2), and tetra(3-hydroxy-3,3-diphenyl-2-propynyl)ethylene (host 3), are characterised by a planar electron-rich central region with bulky substituent groups attached to it. Each substituent contains a hydroxyl group capable of hydrogen bonding. These features enable the inclusion of small organic solvent molecules, with suitable functional groups, within the host framework. The crystal structures of selected inclusion compounds and the a-phases of hosts 1 and 3 are presented. The hydrogen bonding patterns and host-guest interactions are analysed. The packing motif of the host compounds and host conformation within each structure is also discussed. The thermal decomposition behaviour of these compounds was investigated using thermogravimetry and differential scanning calorimetry. The kinetics of desolvation for some of the inclusion compounds was determined using isothermal thermogravimetry. Rate laws describing the desolvation mechanisms are ascribed, and the activation energies determined.